2009
DOI: 10.1155/2009/791432
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Melatonin Against Mitomycin C‐Induced Genotoxic Damage in Peripheral Blood of Rats

Abstract: Mitomycin C (MMC) generates free radicals when metabolized. We investigated the effect of melatonin against MMC-induced genotoxicity in polychromatic erythrocytes and MMC-induced lipid peroxidation in brain and liver homogenates. Rats (N = 36) were classified into 4 groups: control, melatonin, MMC, and MMC + melatonin. Melatonin and MMC doses of 10 mg/kg and 2 mg/kg, respectively, were injected intraperitoneally. Peripheral blood samples were collected at 0, 24, 48, 72, and 96 hours posttreatment and homogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 78 publications
3
8
0
Order By: Relevance
“…Similar to our findings, MMC was reported to be bioactivated by P450 reductase through one electron reduction and produces oxygen radicals (Seow et al 2004). Ortega-Gutiérrez et al (2009) revealed that MMC generated free radicals when metabolized. Activity of anti-oxidant enzymes like superoxide dismutase (SOD) and glutathione peroxidases (GSH-Px) content had declined after exposure to MMC in blood and liver samples of mice (Li et al 2009).…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our findings, MMC was reported to be bioactivated by P450 reductase through one electron reduction and produces oxygen radicals (Seow et al 2004). Ortega-Gutiérrez et al (2009) revealed that MMC generated free radicals when metabolized. Activity of anti-oxidant enzymes like superoxide dismutase (SOD) and glutathione peroxidases (GSH-Px) content had declined after exposure to MMC in blood and liver samples of mice (Li et al 2009).…”
Section: Discussionsupporting
confidence: 90%
“…MLT is also called N-acetyl-5-methoxytryptamine (MLT) and it is synthesized by the pineal gland in the brain where it participates in the regulation of a number of important physiological and pathological processes in mammals (Reiter, 1991). Various studies have confirmed that MLT has a protective effect against DNA damage, although the mechanisms by which MLT produced such protective effects are not clear (Assayed & Abd El-Aty, 2009;Awara et al, 1998;Erenberk et al, 2014;Ferreira et al, 2013;Kontek & Nowicka, 2013;Lialiaris et al, 2008;Ortega-Gutiérrez et al, 2009;Purohit & Rao, 2014;Vijayalaxmi et al, 1995). The aim of this study is to clarify whether MLT has a protective effect against hypoxia at the cytogenetic level by examining SCE formation both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of SCE is responsible for activating the mechanism to repair double strand breakage, including homologous recombination (HB) (Johnson & Jasin, 2000;Stoilov et al, 2002). The increasing rate of SCE reflects the mutagenic effect of stimulants like radiation or chemical drugs, and this effect on the SCE rate can be reversed by genoprotective agents, including MLT (Assayed & Abd El-Aty, 2009;Awara et al, 1998;Kontek & Nowicka, 2013;Lialiaris et al, 2008;Ortega-Gutiérrez et al, 2009). MLT possesses a variety of mechanisms for genoprotective effects, including direct free radical scavenging, regulation of gene transcription for antioxidative enzymes and induction of DNA repair (Fischer et al, 2008;Tomás-Zapico & Coto-montes, 2005;Vijayalaxmi et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many efforts have been made to improve the therapeutic index of MMC using pharmacological strategies, such as the administration of melatonin, curcumin, or flavonoid compound like quercitin. [18][19][20] rhEPO, apart its hematopoietic role, has been shown to prevent several injuries. 21,22 In fact, it has been demonstrated that rhEPO receptors are expressed in many tissues, including heart, kidney, and liver.…”
Section: Discussionmentioning
confidence: 99%